Optimum sow replacement strategies in swine production - Lanzer, Edgar Augusto; Protas, José Fernando da S. (Pesquisa Agropecuaria Brasileira, 2014)
This research deals with the problem of determining optimal disposal strategies for sows in the sense of maximizing the average of weaned piglets per litter per year of the production unit. Methods for determining optimal disposal policies were reviewed and thus applied to a set of data for a production unit located in Santa Catarina. The results indicate that more elaborated sow disposal strategies can increase significantly the reproductive efficiency in swine production at neglegible costs. This efficiency may be somewhat further increased through the discovery of better methods for choosing the reposition females. However, return to research in this area seems to be constrained by the fact that litter size repeatability seems to be low among swine.